Bridging Generations: The Mediating Role of Job Satisfaction in the Relationship Between Adaptation, Loyalty, Culture, and Performance among Gen Z Employees - Rizky Zafira, Yuni; Syahrul Effendi; Hendryadi (Journal of Economics and Business Aseanomics, 2025)
This research aims to test whether employee adaptation, employee loyalty, and organizational culture influence employee performance through job satisfaction among KFC employees in the Cempaka area. This research uses a quantitative associative research approach, which was measured using a SEM PLS-based method with SmartPLS 4. The population of this study were KFC employees in the Cempaka area. The sample was determined based on the census sampling method, with a total sample of 78 KFC employees in the Cempaka area. The data used in this research is primary data. The data collection technique uses a survey method by distributing questionnaires, testing hypotheses using the path coefficient. The research results prove that partially employee adaptation, employee loyalty and organizational culture have no effect on employee performance. Then employee adaptation has no effect on job satisfaction, while employee loyalty and organizational culture have an effect on job satisfaction. Job satisfaction cannot mediate the influence of employee adaptation, employee loyalty, and organizational culture on employee performance